Exploring Thermoelectric Properties in Emergent Carbon Materials - Lucas Lopes Lage; Andrea Latgé (The Journal of Engineering and Exact Sciences)
Since the graphene synthesis several theoretically predicted carbon based materials have become on the spot of experimental factories. Novel compounds were explored creating a family of graphene allotropes, such as graphynes, Metal Organic Frameworks (MOFs), and more recently biphenylene and its derivatives. Each family has its own particularity with possible applications. Here, the Landauer method with Green’s function formalism was used within a Tight-Binding model to obtain electronic properties of such materials. The main results for the thermoelectric coefficients of such materials indicate a high potential application in nanoscopic devices to store/produce energy.